Word Interpretation of â€œSÄ«rÅ«â€ in Alquran and Its Relevance with Halal Tourism - Hendri Hermawan Adinugraha; Ahmad Hasan Asyâ€™ari Ulamaâ€™i; Asep Suraya Maulana (Religia, 2019)
Halal tourism is one of the current trends in sharia business trends (State of the Global Islamic Economy 2017-2018). This proves that the term halal which was formerly just something that is permissible in Islam, has now become a necessity and lifestyle for Muslim communities in the country even on the international scene. Because these tours use halal branding that cannot be separated from Islamic sharia, this study aims to explain the concept of halal tourism in the Qurâ€™anic perspective. This research is a qualitative research through research literature sourced from interpretation books both offline and online, journals relating to halal tourism propositions and other primary text sources. This study uses a descriptive analytical approach. The results of the literature review analysis show that the application of halal concepts in tourism is proof of the flexibility of Islamic sharia at a practical level. The argument regarding the command to consume halal products has been written in the Holy Qurâ€™an, Surat al-Baqarah, verses 162 and 172, and looking for something lawful for every Muslim in daily life is to have a law that must be carried out, this is based on the Prophetâ€™s words: â€œlooking for the lawful is obligatory for every Muslimâ€ (HR Thabrani). The tourism in the Qurâ€™anic perspective is contained in the following verses: Q.S. Al-Mulk verse 15, Q.S. Al-â€™Ankabut verse 20, Q.S. Ali â€˜Imron verses 137 and 191, Q.S. Al-â€™Anâ€™am verse 11, Q.S. An-Naml verse 69, QS. Al-Muâ€™min verses 21 and 64, Q.S. An-Nahl verse 36, Q.S. Ar-Rum verse 42. The sentence Ø³ÙÙŠØ±ÙÙˆØ§ ÙÙÙŠ Ø§Ù„Ù’Ø£ÙŽØ±Ù’Ø¶Ù in the Qurâ€™an other than as a proposition for travel, the sentence instructs people to explore and explore all of Allahâ€™s creation, because Allah also likes aesthetics or beauty. The application of the concept of halal on tourism is always accompanied by the implementation of the concept of thayyib and does not cause damage, because the combination of the concepts of halal and thayyib in travel will result in tourism full of blessings